COMPOSITION AND PROPERTIES OF MINERAL NON-FORMATIONS ON A FILTER SUBSTRATE DURING TREATMENT OF UNDERGROUND WATER FROM IRON AND MANGANESE - Charny, D.; Shevchenko, O.; Nesterovskyi, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Purpose. To determine composition and properties of iron-manganese crusts formed on grainy filtration load granules surface in the process of underground waters cleaning from Fe2+ and Mn2+, and to determine the application limits and perspective trends of the offered water preparation technology development, conditioned by the properties of these crusts. Method. For the analysis of physical and chemical properties of iron-manganese crusts analytical methods are used on the base of leaching and determination of iron and manganese content in solution and for more precise definition of crust qualitative composition an X-ray fluorescent photography spectrometry is used. For determination of crystalline structure an X-ray photography diffractometry was used, and the thickness of film was determined by mechanical micrometry. Processing of the received information and graphic interpretation of data is executed with application of LibreOffice Cacl, Gnumeric and PSPP software. Results. Determined physicochemical characteristics of iron-manganese crust formed on granules surface of grainy filtration load, the metrical sizes of film are determined: thickness and mass, analytically determined by lixiviating contents of iron and manganese in a crust. Manganites, that form a crust, are dispersion characterized; on some occasion considerable amount of roentgenoamorphous phase is formed, and in other - a crystalline form predominates as todorokite. In our opinion, it is determined by correlation of Mn/Fe concentrations in initial water. Results of crust measuring on the granules of filtration load on the water treatment station in town of Uzin is the following: thickness 0,518±0,209 mm; mass 0,0039±0,0004 g, manganese contents and total iron, accordingly, 115,59±4,33 mg/dm3 and 55,33±30,85 mg/dm3. Manganese and iron contents, which were lixiviated from the crusts of filtration load on the water treatment station in Chervona Sloboda village, accordingly: 55,067±10,946 mg/dm3; 100,476±4,284 mg/dm3. Scientific novelty. Firstly possibility of forming catalytic crust (film) from iron-manganese compositions on the filtration load surface is experimentally proved, among those compositions there are higher oxides of manganese in considerable volumes. Having determined their crystalline and chemical structure, it was proved that they provide the effective removal of iron and manganese over the norm contents from water and in a perspective can be used for the removal of a number of low valency cations among which the removal of Са2+ and Вr2+ is experimentally confirmed. Practical significance. Based on the known geobiochemical cycles of iron and manganese a new water treatment technology and also a new filter material with considerable potential of subsequent improvement and application are gotten, unlike classic technologies of manganese removal this method does not require bringing in additional reagents at Mn(II) → Mn(IV) oxidation.